Predicting dietary intake among children classified as overweight or at risk for overweight: Independent and interactive effects of parenting practices and styles. (1st March 2017) - Langer, Shelby L.; Seburg, Elisabeth; JaKa, Meghan M.; Sherwood, Nancy E.; Levy, Rona L.
Abstract: Using baseline data from a randomized controlled pediatric obesity prevention trial, this study sought to examine general parenting style as a potential moderator of the association between feeding-specific parenting practices and child dietary intake. Four hundred and twenty-one parent-child dyads served as participants (49% girls and 93% mothers). Children were, on average, 6.6 years old and either overweight or at-risk for overweight (mean BMI percentile = 84.9). Data were collected in participants' homes. Study staff measured children's height and weight. Parents completed questionnaires designed to assess general parenting styles (authoritative, authoritarian and permissive) and child feeding practices (restriction and monitoring). Child dietary intake was assessed using a 24-h recall system. Outcomes were daily servings of fruits and vegetables, sugar-sweetened beverages (SSB), and unhealthy snacks. Results were as follows: Permissive parenting was inversely associated with fruit and vegetable consumption, and parental monitoring was inversely associated with SSB consumption. There were no other main effects of parenting style or feeding practice on child dietary consumption. Authoritarian parenting moderated the association between restriction and SSB intake (a marginally significant effect after correcting for multiple comparisons). Restriction was inversely associated with SSB consumption when authoritarianism was high but unassociated with SSB consumption when authoritarianism was low. Findings indicate that the parenting practice of monitoring child dietary intake was associated with more healthful consumption regardless of parenting style; interventions may thus benefit from encouraging parental monitoring. The parenting strategy of restricting child dietary intake, in contrast, was associated with lower SSB intake in the context of higher parental authoritarianism but inconsequential in the context of lower parental authoritarianism. This exploratory finding warrants further investigation. Highlights: We studied associations between general parenting styles, specific feeding practices, and child dietary consumption. Greater parental monitoring of child food intake was associated with decreased sugar-sweetened beverage consumption. Greater permissiveness (general parenting style) was associated with decreased fruit and vegetable consumption. Restrictive feeding may be beneficial in the presence of higher levels of authoritarian parenting.